A Study of Trainee Visual Arts Teachers Metaphorical Perception of the Concept of 'The Teacher' and 'The Artist' - (:unkn) unknown (HACETTEPE UNIV, 2015)
The purpose of this research is to examine how students studying at the Fine Arts Education Department Art and Craft Education Department perceive the concepts of being a teacher and an artist through analysis of metaphors. The research study group is based on 205 students studying at Marmara University in 2013-2014. To collect related data and identify the metaphors every trainee teacher has in mind about the concept of 'the teacher' and 'the artist' the participants had to fill in the blanks in two sentences: A Teacher is like a/an ... , because ... ; An artist is like a/an ... , because ... . Metaphor analysis was used in the frame of qualitative method. According to the findings, 181 valid metaphors were detected and classified into 9 categories: teacher as knowledge source, as a mentor, as a shape former, as an expression of love, as a part of life, as a reflection of life, as a leader, as a healer, and as a patient person. The 'artist' metaphors were also classified in 9 categories: enlightening mentor artist, reflecting, creativity/freedom, difference/variability, genuine, history making, being a part of life, self-renewal, and producer artist.
Keywords: trainee fine arts teacher; teacher; artist; metaphor